Brain Protection in Cardiac Surgery Volume 1 - Bonser, Robert S.; Pagano, Domenico; Haverich, Axel.; SpringerLink (Online service) (London : Springer London, 2011)
Brain injury remains one of the most dreaded complications of cardiac surgery. The range of injury is broad; while a stroke may be easily defined and diagnosed, more subtle injuries most definitely occur. There remains debate as to how these are diagnosed and there is a lack of standard definitions allowing inter-study comparison. If we are to have confidence in strategies that may reduce brain injury, we need to have confidence in the end-points used to define that injury. We need to better understand the phenomena associated with neuropsychometric testing; we need to fully elucidate the relationship between structural brain injury, embolism counting, and surrogate biomarkers; and we need an improved understanding of the clinical significance of abnormalities detected on postoperative magnetic resonance imaging. Brain Protection in Cardiac Surgery presents a detailed background of studies of neurological morbidity and neuroprotection from a range of experts in the field of neuroprotection, providing a detailed reference for clinicians in the field. The Editors have detailed connections between the different strands of injury $1 (Bbe it the pathology, the imaging, the clinical and cognitive examination, potential biomarkers $1 (Band have then provided summary reports of treatment strategies that may reduce such injury. As we look to the future, the design of studies attempting to reduce such injury becomes increasingly important and this book provides the fundamental background information to fuel interest, initiate novel prevention and therapeutic strategies, and inform the investigator how to develop and design their research study.s
Keywords: Medicine; Radiology, Medical; Internal medicine; Cardiology; Neurology; Heart -- Surgery; Medicine & Public Health; Cardiac Surgery; Cardiology; Neurology; Neuroradiology; Imaging / Radiology; Internal Medicine